2017
DOI: 10.1016/j.jtusci.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol extract of Tetrapleura tetraptera fruit peels: Chemical characterization, and antioxidant potentials against free radicals and lipid peroxidation in hepatic tissues

Abstract: The chemical and antioxidant properties of the ethanolic extract of Tetrapleura tetraptera fruit peels were investigated. Dried peels of T. tetraptera fruits were extracted with ethanol. The extract was subjected to preliminary phytochemical screening using standard procedures. GC-MS was used in identifying the secondary metabolites. The antioxidant properties of the extract were determined by its ferric reducing activity, 2,2-diphenyl-1-picrylhydrazyl (DPPH) and nitric oxide (NO) radicals scavenging activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 25 publications
2
33
0
1
Order By: Relevance
“…Tetrapleura tetraptera has a long history of use for the traditional management of neurological diseases in West Africa. Studies have shown that its biological effects include antioxidative and anti-inflammatory properties [ 33 , 61 , 62 ] and also, its anticonvulsive [ 30 , 35 ] and anti-ischemic [ 28 ] properties. Polyphenols in Tetrapleura tetraptera may act synergistically against ischemia/reperfusion injury through abatement of oxidative stress, lipid peroxidation, and neurochemical dysfunctions [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetrapleura tetraptera has a long history of use for the traditional management of neurological diseases in West Africa. Studies have shown that its biological effects include antioxidative and anti-inflammatory properties [ 33 , 61 , 62 ] and also, its anticonvulsive [ 30 , 35 ] and anti-ischemic [ 28 ] properties. Polyphenols in Tetrapleura tetraptera may act synergistically against ischemia/reperfusion injury through abatement of oxidative stress, lipid peroxidation, and neurochemical dysfunctions [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its stem, bark, root, leaves, and fruits have various medicinal and nutritional properties [ 30 ]. The medicinal effects of Tetrapleura tetraptera plants have been ascribed to the presence of polyphenol components such as phenols, flavonoids and saponins [ [31] , [32] , [33] ]. The fruit of Tetrapleura tetraptera has been shown to have antihypertensive, anticonvulsive, and cognitive enhancing properties [ [34] , [35] , [36] , [37] ].…”
Section: Introductionmentioning
confidence: 99%
“…Ten grams of T. tetraptera root powder were soaked into 90 ml of absolute ethanol, kept in a shaker (Stuart Scientific Orbital Shaker, Cambridge, UK) with 110 rpm at 37°C for 48 hr (Erukainure et al, ). Suspension was filtered through the Whatman filter paper, and the solvent was evaporated in a rotary evaporator (Laborota 4000 Efficient, Heidolph, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental data also supports the anticonvulsant role of whole T. tetraptera fruit extract or its metabolites (Ojewole 2005;Aderibigbe et al 2007;Adesina et al 2016). Other activities of T. tetraptera include anti-inflammatory, antioxidant, hypoglycaemic, hypolipidaemic, hypokalaemic and central nervous system depressant, among others (Atawodi et al 2011;Lekana-Douki et al 2011;Wahab 2015;Adesina et al 2016;Erukainure et al 2017).…”
Section: Introductionmentioning
confidence: 99%